PENGEMBANGAN E-MODUL TRIGONOMETRI BERBASIS ANDROID UNTUK MENINGKATKAN KEMAMPUAN PENALARAN MATEMATIS SISWA - Fatin, Aiza; Harahap, Muhammad Syahril; Lubis, Roslian (JURNAL MathEdu (Mathematic Education Journal), 2023)
Abstract This development research aims to 1) determine the validity of developing an Android-based trigonometry E-Module, 2) Knowing the practicality of using an Android-based trigonometry E-Module in learning activities, and 3) Knowing the effectiveness of an Android-based trigonometry E-Module to improve students' mathematical reasoning abilities. This research is a Research and Development (R&D) research with a 4D (four D) development model, where this research consists of 4 stages, namely, 1) Defining Phase, 2) Design Phase, 3) Development Phase (Development). ), and 4) the Dissemination Stage. Data collection techniques in this study were questionnaires, tests and documentation. The instruments used include 1) a questionnaire sheet in the form of a validation questionnaire by an expert to see the validity of the product and a student response questionnaire to see the practicality of the product, and 2) a test sheet to see the effectiveness of the product being developed. Validation was carried out by media experts and material experts, then product trials were carried out by looking at the responses to product use and student test results based on students' mathematical reasoning abilities, which were tested on 29 students in class XI MIA 1 SMA N 1 Angkola Timur. Based on the results of this study, the product validity was obtained with an average percentage of 91.05% in the "Very Valid" category, product practicality with an average percentage of 83.53% in the "Practical" category, and product effectiveness with an average percentage of 84, 29% in the “Effective” category. Keywords—Development, E-Module, Mathematical Reasoning Ability